Accuracy of trabecular bone microstructural measurement at planned dental implant sites using cone‐beam CT datasets. Issue 8 (15th April 2013) - Ibrahim, Norliza; Parsa, Azin; Hassan, Bassam; van der Stelt, Paul; Aartman, Irene H.A.; Wismeijer, Daniel
Abstract Objective Cone‐beam CT (CBCT) images are infrequently utilized for trabecular bone microstructural measurement due to the system's limited resolution. The aim of this study was to determine the accuracy of CBCT for measuring trabecular bone microstructure in comparison with micro CT (μCT). Materials and methods Twenty‐four human mandibular cadavers were scanned using a CBCT system (80 μm) and a μCT system (35 μm). Three bone microstructural parameters trabecular number (Tb.N), thickness (Tb.Th) and separation (Tb.Sp) were assessed using CTAn imaging software. Results Intraclass correlation coefficients (ICC) showed a high intra‐observer reliability (≥ 0.996) in all parameters for both systems. The Pearson correlation coefficients between the measurements of the two systems were for Tb.Th 0.82, for Tb.Sp 0.94 and for Tb.N 0.85 (all P's<0.001). The Bland and Altman plots showed strongest agreement in Tb.N (‐0.37 μm) followed by Tb.Th (1.6μm) and Tb.Sp (8.8μm). Conclusions Cone‐beam CT datasets can be used to evaluate trabecular bone microstructure at dental implant sites. The accuracy for measuring Tb.N was the best followed by Tb.Th and Tb.Sp.